C-Reactive Protein: Higher During Acute Psychotic Episodes and Related to Cortical Thickness in Schizophrenia and Healthy Controls - Jacomb, Isabella; Stanton, Clive; Vasudevan, Rohini; Powell, Hugh; O'Donnell, Maryanne; Lenroot, Rhoshel; Bruggemann, Jason; Balzan, Ryan; Galletly, Cherrie; Liu, Dennis; Weickert, Cynthia S.; Weickert, Thomas W. (Frontiers in Immunology, 2018)
There is increasing evidence for the role of inflammation in schizophrenia, yet the stability of increased peripheral inflammation in acute psychosis and the degree to which peripheral inflammation relates to cortical thickness, a measure of the degree of neuropathology, are unknown. In independent samples, we assessed the peripheral inflammation marker C-reactive protein (CRP) to determine the extent to which: 1) CRP was elevated and stable across admissions for acute psychosis, 2) cognition, daily function and symptom severity are characteristic of chronically ill patients with schizophrenia displaying elevated CRP, and 3) CRP levels predict cortical thickness. Study 1 assessed peripheral CRP (primary outcome) and other blood measures in 174/280 people with acute psychosis while Study 2 assessed peripheral CRP, cognition and cortical thickness (primary outcomes), symptoms, and daily function in 85/97 chronically ill patients with schizophrenia and 71/87 healthy controls. In acute psychosis, CRP and neutrophil-to-lymphocyte ratio were significantly elevated relative to a normal cutoff (with 59.8% of patients having elevated CRP) which remained elevated across admissions. CRP was significantly elevated in 43% of chronically ill patients with schizophrenia compared to 20% in controls. Elevated CRP patients displayed significantly worse working memory and CRP was inversely correlated with cortical thickness in frontal, insula and temporal brain regions. This work supports the role of inflammation in psychotic illnesses and suggests that use of peripheral markers (e.g., CRP) in conjunction with diagnosis could be used to identify patients with more cortical neuropathology and cognitive deficits.